Distributed Ledger for Insurance Information Sharing - Franco, Catarina Figueiredo (2020)
The global insurance market has been continually adapting to challenges and new opportunities. Nowadays, most insurances have centralized systems, which could be inefficient and less transparent. Moreover, such solutions can also create distrust and conflicts of interest between insurance companies and policyholders. Other recent technologies can improve existing business models. Distributed ledger technology, in specific, can offer to the insurance sector transparency and efficiency at another level, without compromising the security and privacy that the sector requires. Distributed ledger technology avoids the single point of failure problem. This protection increases the security level of the system since it is more demanding, or nearly impossible, to compromise the data in the ledger. This document presents a comprehensive overview of different distributed ledger technologies, which lead to the decision of the one that best suits the business case. The prototype design and implementation are fully described, along with the tests and the evaluation of the results. A solution was explored to create a decentralized data storage, for workers' insurance information sharing, using a distributed ledger technology. This decentralized approach diminishes the responsibilities of the central authority by removing the project dependence upon centralized computing resources for storing and processing.